Association between phytosterol intake and colorectal cancer risk: a case–control study. Issue 6 (6th April 2017) - Huang, Jing; Xu, Ming; Fang, Yu-Jing; Lu, Min-Shan; Pan, Zhi-Zhong; Huang, Wu-Qing; Chen, Yu-Ming; Zhang, Cai-Xia
Abstract: A study in rodent models showed that phytosterols protected against colon carcinogenesis, probably by inhibiting dysregulated cell cycle progression and inducing cellular apoptosis. However, epidemiological studies on the relationship between phytosterols and colorectal cancer risk are quite limited. The aim of this study was to investigate dietary phytosterol intake in relation to colorectal cancer risk in the Chinese population. A case–control study was conducted from July 2010 to June 2016, recruiting 1802 eligible colorectal cancer cases plus 1813 age (5-year interval) and sex frequency-matched controls. Dietary information was collected by using a validated FFQ. The OR and 95 % CI of colorectal cancer risk were assessed by multivariable logistic regression models. A higher total intake of phytosterols was found to be associated with a 50 % reduction in colorectal cancer risk. After adjusting for various confounders, the OR of the highest quartile intake compared with the lowest quartile intake was 0·50 (95 % CI 0·41, 0·61, P trend <0·01) for total phytosterols. An inverse association was also found between the consumption of β -sitosterol, campesterol, campestanol and colorectal cancer risk. However, stigmasterol intake was related to an increased risk of colorectal cancer. No statistically significant association was found between β -sitostanol and colorectal cancer risk. Stratified analysis by sex showed that the positive association of stigmasterol intake with colorectal cancer risk was found only in women. These data indicated that the consumption of total phytosterols, β -sitosterol, campesterol and campestanol is inversely associated with colorectal cancer risk in a Chinese population.